Study of B Meson Production in p plus Pb Collisions at √sNN=5.02 TeV Using Exclusive Hadronic Decays - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Eroe, J.; Flechl, M.; Friedl, M.; et al. (AMER PHYSICAL SOC, 2016)
The production cross sections of the B+, B-0, and B-s(0) mesons, and of their charge conjugates, are measured via exclusive hadronic decays in p + Pb collisions at the center-of-mass energy root s(NN) = 5.02 TeV with the CMS detector at the CERN LHC. The data set used for this analysis corresponds to an integrated luminosity of 34.6 nb(-1). The production cross sections are measured in the transverse momentum range between 10 and 60 GeV/c. No significant modification is observed compared to proton-proton perturbative QCD calculations scaled by the number of incoherent nucleon-nucleon collisions. These results provide a baseline for the study of in-medium b quark energy loss in Pb + Pb collisions.
Keywords: MONTE-CARLO; ENERGY-LOSS; Physics